(untitled) (Andamios, Revista de Investigación Social, 2013)
The article confronts the problem of violence departing from the answers given by contemporary society: Utilizing Oliver Stone’s film, paradigmatic in the treatment of the aggression and the violence. The author analyses the subject, tests the answers to topics ranging from the mediatic treatment and the trivialitation to the point of becoming critic to the power. The research exhibits a recount of causes that justifies the treatment of violence as a filmic criticism of the postmodern perception of the reality: Before the spirit, science and truth crisis.